SHOULD THE ACCOUNTING ENTITY BE PERSONIFIED? - Kell, Walter G. (The Accounting Review, 1953)
The most important underlying assumption of accounting is the unit for which accounting has responsibility. The accounting unit, generally referred to as the accounting entity, forms the basis for the accounting records. It determines the boundaries of relevant and irrelevant data, and it has a direct effect upon the theory of accounting used in recording the activities of the entity. Despite the importance of this basic concept, there has been a definite lack of clear and concise determination of the exact nature of an accounting entity once the entity has been selected, and a seemingly endless controversy has ensued over the entirely irrelevant question of whether the corporate accounting entity is based on fact or whether it is based on fiction. The factual basis of the accounting entity is also attacked on legal grounds. It is pointed out that the courts do not regard an unincorporated entity as being separate and distinct from its owners, and it is charged that the courts frequently pierce the veil of the corporate entity.